STUDENTS IMPROVEMENT IN READING COMPREHENSION THROUGH PQRST (Preview, Question, Read, State, Test) TECHNIQUE - Erni Yessi; Sahrawi Sahrawi; Dian Shinta Sari (Journal of English Language Teaching and Education (JELTE), 2024)
This study investigates whether implementing the PQRST technique can improve students' reading abilities at SMP Muhammadiyah 2 Pontianak. Through careful observation and measurement, it was noted that students' comprehension showed a substantial improvement. Specifically, their average score rose significantly from 25.6 to 89.7. This outcome strongly suggests that employing the PQRST technique is highly effective in enhancing students' reading comprehension levels. These findings underscore the technique's practical value in educational settings, emphasizing its potential to positively impact student learning outcomes and academic performance in reading comprehension at the junior high school level.Keyword: PQRST Technique, Reading Ability, Classroom Action Research